Pengaruh Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus Perusahaan Manufaktur terdaftar di Bursa Efek Indonesia Peridoe 2016 - 2020) - Dina Fitria; Arlis Dewi Kuraesin (UNIVED Press, 2022)
This study aims to determine the effect of profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange. The measurement of firm value in this study is Price to book value (PBV). The sample in this study were 36 companies which were determined by purposive sampling. The population in this study was 180 companies manufacturing companies on the Indonesia Stock Exchange for the 2016-2020 period. The type of data used is secondary data from the website https://www.idx.co.id/. The analytical technique used in this study is multiple linear regression analysis and hypothesis testing with the help of SPPS version 25. The results of the partial test found that profitability had a significant positive effect on firm value.